Tunable first order transition in La(Fe, Cr, Si)13 compounds: Retaining magnetocaloric response despite a magnetic moment reduction. (15th August 2019) - Moreno-Ramírez, Luis M.; Romero-Muñiz, Carlos; Law, Jia Yan; Franco, Victorino; Conde, Alejandro; Radulov, Iliya A.; Maccari, Fernando; Skokov, Konstantin P.; Gutfleisch, Oliver
Abstract: Materials with a large magnetocaloric response require a large magnetic moment. However, we show in this paper that it is possible to retain both the isothermal entropy change and the adiabatic temperature change even using dopants that reduce the magnetic moment of the parent alloy, provided that the first order character of the transition is enhanced. In this work, a combination of first-principles calculations, experimental determination of the magnetocaloric response (direct and indirect) as well as a new criterion to determine the order of the phase transition are applied to Cr-doped La(Fe, Si)13 compounds. Despite a reduction in magnetic moment, the magnetocaloric response is retained up to x ≈ 0.3 in LaFe11.6-x Crx Si1.4 . Unlike other transition metal dopants, Cr occupy 8b sites and couple antiferromagnetically to Fe atoms. The cross-over of first to second order transition is achieved for a Cr content of x = 0.53, larger in comparison to other dopants (e.g. Ni or Mn). A direct relation between the first order character and the hysteresis is observed. Graphical abstract: Image 1